2020
DOI: 10.1002/stc.2603
|View full text |Cite
|
Sign up to set email alerts
|

Displacement monitoring model of concrete dams using the shape feature clustering‐based temperature principal component factor

Abstract: Summary The mathematical monitoring model‐based interpretation of recorded quantities, especially of displacements, is essential for the structural health diagnosis of concrete dams. In practice, dam displacements are frequently interpreted and predicted by the hydraulic, seasonal, and time model, which considers the thermal deformation effect of a dam body by the periodic harmonic factor. The main purpose of this paper is to replace this factor with the measured temperatures of a dam body. This approach is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…2. According to equation (17), the integrated SSI between the model-fitted displacement time series of the analyzed monitoring point and the measured displacement time series of all the other monitoring points in the same cluster can be obtained. To achieve the optimization objectives of the fitting MSE and SSI at the same time, the reciprocal value, RS = 1=SSI, is coupled with the fitting MSE to form the overall optimization objective function.…”
Section: Spatial Association-coupled Double Objective Optimization Fu...mentioning
confidence: 99%
See 1 more Smart Citation
“…2. According to equation (17), the integrated SSI between the model-fitted displacement time series of the analyzed monitoring point and the measured displacement time series of all the other monitoring points in the same cluster can be obtained. To achieve the optimization objectives of the fitting MSE and SSI at the same time, the reciprocal value, RS = 1=SSI, is coupled with the fitting MSE to form the overall optimization objective function.…”
Section: Spatial Association-coupled Double Objective Optimization Fu...mentioning
confidence: 99%
“…The massive temperature observation data can also be extracted by principal component analysis (PCA), and only a small number of useful principal components are then used to establish the HT PCA T model. To further improve the accuracy of the thermal deformation effect, Wang et al 17 suggested conducting a shape feature-based spatial clustering for the measured dam temperature field, and principal components can then be extracted from each cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [1] proposed the special statistical models for the displacements of high arch dams during their initial impoundment periods by improving estimations of the non-stationary thermal and the non-monotonic timedependent effects. Wang et al [19] presented a shape feature-based spatial clustering method for the dam temperature field, and established a displacement monitoring model of concrete dams using the shape feature clustering-based temperature principal component factor.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the accuracy of the dam thermal deformation effect, some researchers have proposed replacing the periodic harmonic factor in the HST model with the measured dam temperatures, and the hydraulic, thermal, and time (HTT), HT PCA T (improved HTT model with temperature factors extracted by principal component analysis), HT S-PCA T (further improved HT PCA T model with the shape feature clustering-based temperature principal component factors), HST-grad, and HST-layer models have been proposed. [15][16][17][18] In addition, to interpret the observed nontypical deformation behavior of some concrete dams, new influencing factors have been introduced into the HST or HTT models, as in the case of the hydraulic, thermal, crack, and time (HTCT) model for the Chencun arch dam with horizontal cracks, 19 the hydraulic, hysteretic, seasonal, and time (HHST) model for interpreting the hysteretic hydraulic deformation of the Jinping-I arch dam, 20 and the hydraulic, seasonal, thermal, and time (HSTT) model for considering the influence of European heat waves in 2003. 21 These models were mainly established by multiple linear regression (MLR) and stepwise regression methods and had explicit mathematical expressions.…”
Section: Introductionmentioning
confidence: 99%